Model Pendidikan Moral Digital Berbasis Pemikiran Hamka: Integrasi Metode Diskusi Dan Akhlak Untuk Penguatan Etika Digital Peserta Didik - Tatang Suhandar; Dedi Kuswandi; Agus Wedi (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2025)
Abstract : This study analyzes the application of Hamka’s educational method particularly the use of dialogue-based discussion and moral cultivation (akhlak) as a foundation for developing students’ digital ethics and moral literacy in the contemporary technological era. This research employs a qualitative library-research approach using thematic analysis of Hamka’s major works and relevant scholarly articles. The findings indicate that Hamka’s concept of discussion, which emphasizes open dialogue, rational inquiry, and deep understanding, is highly relevant for digital-age education in fostering critical thinking, ethical awareness, and the ability to evaluate the moral implications of online behavior. Meanwhile, Hamka’s emphasis on akhlak including honesty, etiquette, responsibility, and self-restraint functions as a value-based framework to guide digital ethical conduct in addressing misinformation, hate speech, and moral degradation in online environments. This study concludes that integrating discussion-based learning with moral cultivation offers a contextual and comprehensive model for digital moral education suited to the needs of 21st-century learners. It contributes to Islamic education theory in the digital era and provides an implementable model for teachers to nurture civilized, ethical digital behavior among students. Keywords: Hamka, educational method, discussion, akhlak, digital ethics, moral literacy